2011
DOI: 10.1084/jem.20091473
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting helminth infection induces inhibition of innate pulmonary anti-tuberculosis defense by engaging the IL-4 receptor pathway

Abstract: Preexisting helminth infection impairs immunity against subsequent M. tuberculosis infection, in part by inducing alternatively activated macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
175
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(194 citation statements)
references
References 58 publications
13
175
2
4
Order By: Relevance
“…Evidence suggests that a skewed Th2 response caused due to S. mansoni infection compromises protection conferred by M. bovis BCG vaccination in humans (7-9) and in mice systemically infected with Mtb (12). Similarly, other models of helminth coinfections such as Nippostrongylus brasiliensis, a rodent intestinal helminth that migrates to the lung, also drives Th2 responses and generation of alternatively activated macrophages in the lung, resulting in impaired resistance to Mtb (27). Interestingly, while helminth coinfections increase M. bovis BCG (11) and Mtb (27) lung burden, the increase in mycobacterial burden is often transient (27) and moderate (about 1 log higher in coinfected hosts) (11,27), suggesting that the effect of helminth coinfections on Mtb control is not profound enough to fully explain the increased severity of TB in helminth-coinfected individuals observed in TB endemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that a skewed Th2 response caused due to S. mansoni infection compromises protection conferred by M. bovis BCG vaccination in humans (7-9) and in mice systemically infected with Mtb (12). Similarly, other models of helminth coinfections such as Nippostrongylus brasiliensis, a rodent intestinal helminth that migrates to the lung, also drives Th2 responses and generation of alternatively activated macrophages in the lung, resulting in impaired resistance to Mtb (27). Interestingly, while helminth coinfections increase M. bovis BCG (11) and Mtb (27) lung burden, the increase in mycobacterial burden is often transient (27) and moderate (about 1 log higher in coinfected hosts) (11,27), suggesting that the effect of helminth coinfections on Mtb control is not profound enough to fully explain the increased severity of TB in helminth-coinfected individuals observed in TB endemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…Worms, through the immune responses they evoke, have been suggested as one factor that can impair BCG vaccine efficacy and increase susceptibility to mycobacterial infection (6,35). In support of this, there is ample evidence that worms and worm products can counteract Th1 immunity and downmodulate inflammatory responses to secondary Ags (36).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these responses can counteract Th1 development. Accordingly, worm infection is proposed to impair immune responses that control mycobacteria (4)(5)(6). Infection with worms has also been associated with a reduced ability to respond to BCG vaccination (7,8).…”
mentioning
confidence: 99%
“…Thus, an impaired CD8 T cell effector response to vaccinia virus has been observed in a Schistosoma mansoni-infected host (47). More recently, it has been shown that IL-4 produced during a parasitic infection with Nippostrongylus brasiliensis impairs the innate immune response to a bystander infection with Mycobacterium tuberculosis (48). The IL-4-induced decreased antimicrobial peptide secretion by keratinocytes would be one of the potential mechanisms responsible for this increased susceptibility (49).…”
Section: Discussionmentioning
confidence: 99%